Association between Systemic Lupus Erythematosus and Primary Biliary Cholangitis - Toru Shizuma (Medical Science: Trends and Innovations Vol. 11, 2025)
Liver dysfunction in patients with systemic lupus erythematosus (SLE) includes liver injury caused by SLE itself, and drug-induced and other comorbid liver diseases, such as primary biliary cholangitis (PBC), an autoimmune liver disease. The study aimed to conduct a literature review of clinical or genetic studies and case reports regarding the comorbidity of SLE and PBC. Scientific reports written in English and Japanese were searched in the PubMed and Japana Centra Revuo Medicina databases, respectively, to retrieve studies on SLE and PBC comorbidity published between 1980 and 2024. The incidence of PBC in patients with SLE is 0%–2.7%, and that of SLE in patients with PBC is 0%–3.7%. Although the causal relationship between SLE and PBC remains obscure, recent Mendelian randomization analyses from genome-wide association studies (GWASs) indicated positive causal effects between SLE and PBC. Among the 28 reported cases of SLE and PBC comorbidity, 53.6% (15/28) were first diagnosed with PBC, and 35.7% (10/28) with SLE; meanwhile, 10.7% (3/28) were diagnosed with SLE and PBC simultaneously. Sjogren’s syndrome was observed to be the most common complication (17.9%, 5/28). Two patients had familial PBC, and one concurrently developed hepatocellular carcinoma. Among the three patients who died, two presented with liver failure secondary to PBC exacerbation. According to the 28 reported cases of SLE and PBC comorbidity, the prognosis may be relatively favorable for patients, except for those with liver failure. The causal relationship between SLE and PBC remains obscure; however, some genetic studies using GWAS indicated positive causal effects. Further clinical and experimental studies are necessary to examine SLE and PBC pathophysiology.